Bay leaf essential oils inhibited microbial growth and exerted potential preservation effects on tofu - Alwani Hamad; Asmiyenti Djaliasrin Djalil; Eka Yuliani Saputri; Nur Yulianingsih; Dwi Hartanti (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
Cattle manure contains high organic matter, so that this material is commonly used as plant nutrients in a form of organic fertilizer. In order to get a better understanding on the use of cow manure, the objectives of this research are (1) to determine the influence of liquid waste and solid livestock as fertilizer on soil quality and (2) to study the effect of both liquid and solid fertilizer on coffee plant growth. In this research, Completely Randomized Design (CRD) was employed as a research design, while data analysis was conducted using ANOVA. The F statistical test was applied to measure whether all independent variables could influence the dependent variable by using 5% and 1% (Alpha) degrees. The results showed that one time application of livestock wastewater improved C-organic chemical properties, N, P, CEC, Ca and Mg while soil chemical properties of pH, K, Na decreased. Two times application of livestock liquid fertilizer treatment improved soil chemical properties pH, N total, Ca, Mg and saturation bases. As for solid waste, one time treatment increased chemical properties of pH, C organic, N total, Ca and saturation of the base. The two times treatment could improve soil chemical properties of pH, N. total, P, Ca, Mg, base number and base saturation. Liquid waste fertilizer also found to provide significant effect on plant height and coffee plants quality. Additionally, (3) solid waste (compost) was found to have a significant effect on plant height, plant height rate and number of buds.